Factors associated with the willingness to quit smoking among a cohort of university students in the KSA. Issue 2 (April 2016) - Almogbel, Yasser S.; Abughosh, Susan M.; Almeman, Ahmad A.; Sansgiry, Sujit S.
الملخص: أهداف البحث: هدفت هذه الدراسة إلى تحديد العوامل التي يمكن بها التنبؤ بالاستعداد للإقلاع عن التدخين بين مجموعة من الطلبة السعوديين. طريقة البحث: تم في هذه الدراسة المقطعية توزيع استبانة على مجموعة من الطلبة الذكور من ثلاثة مراكز للتعليم العالي. خضعت البيانات المستحصلة للتحليل ثنائي المتغير واختبارات الانحدار اللوجستية لتقييم العوامل المرتبطة بالاستعداد للإقلاع عن التدخين. النتائج: كان ٢٤٪ من بين الـ ٤٦٧ متجاوب للاستبانة مدخنين حاليين٬ بينما كان ٦٥٪ من بين هؤلاء المدخنين لديهم الرغبة في الإقلاع عن التدخين. تبين من التحليل ثنائي المتغير أن المحاولات السابقة للإقلاع عن التدخين، ورسائل مكافحة التدخين في التلفاز والصحف كان لها علاقة وثيقة بالقابلية للإقلاع عن التدخين. كما بين التحليل الانحداري اللوجستي متعدد المتغيرات أن متغيرا واحدا فقط كان مؤشرا ذا قيمة إحصائية في التنبؤ بقابلية الإقلاع عن التدخين٬ وهو وجود محاولة سابقة للإقلاع عن التدخين. الاستنتاجات: تبين نتائج هذه الدراسة أن الطلبة السعوديين المدخنين الذكور لديهم الرغبة في الإقلاع عن التدخين، وقد بذلوا محاولة سابقة غير ناجحة في الإقلاع عنه وهم على استعداد لإعادة المحاولة. ينبغي استحداث البرامج الناجحة لهذا الغرض فيما يخص طلبة الجامعة الذكور المدخنين في المملكة العربية السعودية لمساعدتهم على تحقيق رغبتهم في الإقلاع عن التدخين وعدم العودة إليه. Abstract: Objectives: The aim of this study was to determine the predictors of the willingness to quit smoking among a cohort of male Saudi students. Methods: In this cross-sectional study, a questionnaire was administered to a cohort of male students that were recruited from three institutes of higher education. Using the retrieved data, bivariate analysis and logistic regression tests were performed to assess the factors associated with the willingness to quit smoking. Results: Of 467 participants, 24% of respondents were current smokers, while 65% of these smokers were willing to quit smoking. In the bivariate analysis, past attempts to quit smoking and the anti-smoking messages on TV and in newspapers were significantly associated with the willingness to quit smoking. Only one variable – past attempts to quit smoking – was a significant predictor of the willingness to quit smoking, as shown by the multivariate logistic regression analysis. Conclusion: The findings of this study indicate that Saudi male students who smoke are willing to quit smoking; having unsuccessfully attempted to quit smoking in the past, they are willing to try again. Successful programs should be developed for male university students in KSA to assist them in their quest to quit smoking and maintain cessation.